Potential of Conditioned Medium of hATMSCs in Aging Cells Model - Wahyu Widowati; Rachmawati Noverina; Wireni Ayuningtyas; Dedy Kurniawan; Seila Arumwardana; Hanna Sari W Kusuma; Rizal Rizal; Dian Ratih Laksmitawati; Ratih Rinendyaputri; Rilianawati Rilianawati; Ahmad Faried (HAYATI Journal of Biosciences, 2022)
Skin aging is caused by the exposure cumulative of ultraviolet radiation, it leads reactive oxygen species (ROS) production in the skin. The conditioned medium of human Adipose Tissue-derived Mesenchymal Stem Cells (hATMSCs) can scavenge free radicals and increase the survival rate of skin cells under oxidative stress. This study examined the protective effects of Conditioned Medium (CM) of hATMSCs in H2O2-induced human skin fibroblast cell line (BJ). The aging cells model using H2O2-induced BJ cells were added CM-hATMSCs in concentrations (0, 10, 30%) and incubated in various time, furthermore BJ cells induced by various H2O2 concentrations (0, 50, 100, 200 µM) incubated for 1 h. The anti-aging potential were measured including viability, ROS and collagen levels in BJ cells which treated CM-hATMSCs. The median inhibitory concentration (IC50) of H2O2 on BJ cells for 1 h incubation was 107.87 μM and 91.25 μM for 10 min incubation. CM-hATMSCs increased the viability on aging model cells. CM-hATMSCs concentration 30% increased the viability of H2O2 50, 100, 200 µM-induced BJ cells. CM-hATMSCs concentration 25% decreased ROS, increased collagen level in H2O2 50, 100, 200 µM-induced BJ cells. CM-hATMSCs increase the viability cells, collagen level and decrease ROS level in aging model cells.